Hydrometallurgical extraction of Al and Si from kaolinitic clays - Pinna,Eliana G. (2017)
Abstract Herein is presented the results of a study on the hydrometallurgic extraction and recovery of aluminum and silicon by leaching of kaolinitic clays with HF. The studied extraction parameters were: temperature, reaction time, solid/liquid ratio, concentration, and precipitating agent mass. In the leaching process, mineral dissolutions near 100% were obtained when working at 348 K, solid/liquid ratio 2% w/v, HF 12% v/v, for 120 minutes. The HF leach liquor generated from the dissolution of kaolinitic clays contains H2SiF6and H3AlF6. Studies were conducted to recover the two valuable fluorides as K2SiF6and Na3AlF6by precipitation with alkaline salts from the leach liquor. Phases of precipitated fluorides were identified by XRD and surface morphology by SEM. The purity of the K2SiF6precipitate was 98.8%, whereas for Na3AlF6, it was 89.3%. Also, both synthesized solids are of high commercial value due to their industrial applications.